2014
DOI: 10.4049/jimmunol.1302392
|View full text |Cite
|
Sign up to set email alerts
|

TRIL Is Involved in Cytokine Production in the Brain following Escherichia coli Infection

Abstract: TLR4 interactor with leucine-rich repeats (TRIL) is a brain-enriched accessory protein important in Toll-like receptor 3 and 4 signalling. Here we generated TRIL-deficient mice and examined TLR responses in vitro and in vivo. We found a role for TRIL in both TLR4 and TLR3 signalling in mixed glial cells, consistent with the high level of expression of TRIL in these cells. We also found that TRIL is a modulator of the innate immune response to LPS challenge and E.coli infection in vivo. TRIL-deficient mice prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…In contrast to the hematopoietic defects observed in Xenopus Tril morphants, mice lacking tril show impaired cytokine production in the brain in response to infection, but do not show gross developmental defects (Wochal et al, 2014). Tril may have subtle functions during mammalian development that have not yet been examined or other molecules present in mice, but not in Xenopus, may compensate for loss of Tril.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast to the hematopoietic defects observed in Xenopus Tril morphants, mice lacking tril show impaired cytokine production in the brain in response to infection, but do not show gross developmental defects (Wochal et al, 2014). Tril may have subtle functions during mammalian development that have not yet been examined or other molecules present in mice, but not in Xenopus, may compensate for loss of Tril.…”
Section: Discussionmentioning
confidence: 66%
“…1A). Tril is a transmembrane protein that functions as a coreceptor for Toll-like receptor (Tlr)3 and Tlr4 to mediate innate immune responses in the brain of adult mammals (Carpenter et al, 2009(Carpenter et al, , 2011Wochal et al, 2014). The extracellular domain contains multiple leucine-rich repeats (LRRs) and a fibronectin type III domain (FN), while the intracellular domain (ICD) contains no known signaling motifs (Fig.…”
Section: Results Tril Is a Downstream Target Of Gata2 That Is Expressmentioning
confidence: 99%
“…In vitro studies showed that the extracellular domain of Tril interacts directly with Tlr4, and with its ligand, LPS, suggesting that it functions primarily to enhance ligand/receptor affinity (7). Subsequent in vitro studies showed that Tril plays a similar role in regulating Tlr3 signaling, and in vivo studies confirmed that Tril is essential for maximal Tlr3-and Tlr4-dependent cytokine production in the brain in response to bacterial infection (8,9).…”
Section: Discussionmentioning
confidence: 97%
“…While Tlrs are known to play non-immune roles in developmental patterning and morphogenesis in insects, evidence that vertebrate Tlr signaling is required for early development is lacking (12). Recent studies, however, have shown that Tlr signaling is required for normal neurogenesis, axonal growth and structural plasticity in the developing and adult brain (11), where Tril is highly expressed (9). Very little is known about the signaling pathways that are initiated by Tlrs to mediate these non-immune effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation